Social media strategy : a practical guide to social media marketing and customer engagement - Atherton, Julie (Business strategist) (London ; New York, NY : Kogan Page, 2023)
"Social media marketing is no longer optional. This book unpacks the winning formula for effective social media marketing complete with comprehensive updates and latest developments. Social Media Strategy contains the latest insights on influencer marketing, new channel explosion and diversification, privacy and behaviour, strategy development and new case studies and interviews. This second edition demonstrates how to design, activate and measure a clear social media strategy which is directly accountable to your wider business objectives. Providing a simple, structured way to create integrated customer engagement and social media campaigns that work, Social Media Strategy delivers practical guidance on key areas, such as identifying and targeting audience segments, a simple ABC (audience, brand, campaign) model, methods of two-way community engagement, reputation management, being present on the right channel, brand purpose, and identifying the relevant tools and platforms to audit, track and measure business impact and customer engagement. With example templates, interviews and global case studies including National Geographic, Lush, South West Airlines, Dreams, Mumsnet and more, this bestselling guide delivers a long-term solution for maximizing social media led business development for any business"--
Includes bibliographical references and index.
Keywords: Internet marketing; Marketing channels; Social media